Currency co-movements in Asia-Pacific: The regional role of the Renminbi - Daniela Marconi (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
The internationalization of China's currency, the renminbi (RMB) bolsters the growing economic and political influence of China in the Asia-Pacific region. This paper assesses the evolution of RMB exchange rate co-movements against the US dollar (USD) within the region. While the RMB's influence is growing, it is also found to be asymmetric and varying over time depending on the global movement of the USD. The trend is strong when the USD depreciates, but fades when the USD appreciates.
URN:NBN:fi:bof-201706141353
Keywords: F31; F33; 330